Measure up - Chapman, Sital Gorasia (Chapman, Sital Gorasia. Math adventurers., 2023)
"Beep and Boots have an exciting, fun-packed day planned at the amusement park. The pals cannot wait to enjoy all the rides together. But when they check their heights, Boots is not tall enough to go on a lot of the rides. And going to an amusement park is no fun if you can't share it with friends. Will Beep be able to come up with a solution so the pair can go on the really high Star Drop ride?"--